1966
DOI: 10.1111/j.1365-2478.1966.tb02245.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sectional Auto‐correlogram and the Sectional Retro‐correlogram *

Abstract: The auto-correlation function of a seismic trace contains information on all the multiple reflection activity present in the trace.The interpretation of this information is facilitated by the arrangement of autocorrelation functions in cross-sectional form, in the manner of a normal record section. This is the concept of the Sectional Auto-Correlogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

1974
1974
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
0
15
0
2
Order By: Relevance
“…For a strong surface primary reflection (12) generally gives by far the largest contribution to TKf(&L + El) ( see appendix I and also Anstey and Newman 1966). Comparison of (9~) with (12) suggests to replace RO * fi by cc .…”
Section: Developmentofthetheorybehindtheapplied Proceduresmentioning
confidence: 92%
“…For a strong surface primary reflection (12) generally gives by far the largest contribution to TKf(&L + El) ( see appendix I and also Anstey and Newman 1966). Comparison of (9~) with (12) suggests to replace RO * fi by cc .…”
Section: Developmentofthetheorybehindtheapplied Proceduresmentioning
confidence: 92%
“…Ceci est bien connu (Anstey 1966, J ac k son 1968, Bourrouilh 1970, Fontanel et Grau 1971 La figure 4 présente encore un cas de traitement ayant réussi de facon satisfaisante. L'exploitation de la comparaison des autocorrélogrammes est ' immédiate: il convient cependant de signaler que la grande largeur apparente de l'axe focal de I'autocorrélogramme après traitement est simplement due à une diffusion dans l'emulsion photographique liée à la forte luminance de l'axe focal.…”
Section: A) -Controle Optique Des Traitements De Deconvolution Et De unclassified
“…Au cours d'une seconde opération qui voit ce spectre de puissance placé à son tour dans le plan-objet, l'analyse spectrale, toujours pratiquée en optique sphérocylindrique, donnera donc l'autocorrélation de la trace. Ceci est bien connu (Anstey 1966, J ac k son 1968, Bourrouilh 1970, Fontanel et Grau 1971 et nous nous proposons seulement ici de décrire une application particulière de cette manipulation qui va permettre à la calculatrice optique de mettre ses qualités de souplesse et de commodite au service des calculatrices numériques en apportant la possibilité, par un test immédiat pratiqué au niveau des documents d'exploitation eux-mêmes, d'une appréciation rigoureuse de l'efficacité des traitements par ordinateurs.…”
Section: A) -Controle Optique Des Traitements De Deconvolution Et De unclassified
“…It has been recognized that the surfacerelated multiples are always dominating multiple energy in seismic data. Theoretical work on surface-related multiple modelling and elimination in 1-D and multidimensional medium has been made by Anstey et al [26] , Riley et al [27] , Kennett et al [28] , and Berkhout et al [15∼16] . Verschuur et al [17∼19] suggested the adaptive surface-related multiple elimination procedure with applications to field data.…”
Section: Introductionmentioning
confidence: 99%